The Impact of Type 2 Diabetes Mellitus on Non-Surgical Periodontal Treatment: A Non-Randomized Clinical Trial - Belizário, Lícia Clara Garcia [UNESP]; Figueredo, Carlos Marcelo S.; Rodrigues, João Victor Soares [UNESP]; Cirelli, Thamiris; de Molon, Rafael Scaf [UNESP]; Garcia, Valdir Gouveia; Theodoro, Letícia Helena [UNESP] (MDPI, 2024)
Background/Objectives: Periodontitis (P), a chronic inflammatory condition that affects the supportive tissues around the teeth, is three to four times more prevalent in individuals with diabetes mellitus (DM), with a direct correlation between its severity and the levels of glycosylated hemoglobin (HbA1c). This study aimed to evaluate the periodontal clinical parameters following non-surgical periodontal treatment (NSPT) in P patients with or without type 2 DM. Methods: Forty patients with P were divided into two groups: Group DM/P and Group P. All the patients were assessed at baseline and at 90 and 180 days after receiving NSPT. The parameters evaluated included the HbA1c level, plaque index (PI), probing pocket depth (PPD), clinical attachment level (CAL), and bleeding on probing (BoP). A statistical analysis was performed with a significance level set at α = 5%. Results: There were significant differences in the HbA1c levels between the DM/P and P groups at baseline, 90, and 180 days, as expected. Importantly, the HbA1c levels did not change after NSPT. Group P showed a significant reduction in both the PI and the BoP values at 90 and 180 days (p < 0.05). In contrast, Group DM/P demonstrated a significant increase in the percentage of sites with a PPD ≥ 5 mm at 180 days (p < 0.05). Additionally, Group P exhibited an increase in sites with a PPD ≤ 4 mm and a decrease in sites with a PPD ≥ 5 mm at both 90 and 180 days (p < 0.05). Conclusions: Our findings suggest that DM may compromise the effectiveness of NSPT, potentially hindering favorable outcomes during the follow-up period.
Keywords: diabetes mellitus; glycated hemoglobin; periodontal disease; periodontitis; scaling and root planing